Padres e hijos - Turgenev, Ivan Sergeevich, 1818-1883 (Akal bolsillo, 2011)
Arkady Kirsanov has just graduated from the University of Petersburg and returns with a friend, Bazarov, to his father's modest estate in an outlying province of Russia. The father gladly receives the two young men at his estate, called Marino, but Nikolai's brother, Pavel, soon becomes upset by the strange new philosophy called "nihilism" which the young men advocate. Nikolai feels awkward with his son at home, partially because Arkady's views have dated his own beliefs"